Loss of function of TET2 cooperates with constitutively active KIT in murine and human models of mastocytosis. - Serena De Vita; Rebekka K Schneider; Michael Garcia; Jenna Wood; Mathilde Gavillet; Benjamin L Ebert; Alexander Gerbaulet; Axel Roers; Ross L Levine; Ann Mullally; David A Williams (PLoS ONE)
Systemic Mastocytosis (SM) is a clonal disease characterized by abnormal accumulation of mast cells in multiple organs. Clinical presentations of the disease vary widely from indolent to aggressive forms, and to the exceedingly rare mast cell leukemia. Current treatment of aggressive SM and mast cell leukemia is unsatisfactory. An imatinib-resistant activating mutation of the receptor tyrosine kinase KIT (KIT D816V) is most frequently present in transformed mast cells and is associated with all clinical forms of the disease. Thus the etiology of the variable clinical aggressiveness of abnormal mast cells in SM is unclear. TET2 appears to be mutated in primary human samples in aggressive types of SM, suggesting a possible role in disease modification. In this report, we demonstrate the cooperation between KIT D816V and loss of function of TET2 in mast cell transformation and demonstrate a more aggressive phenotype in a murine model of SM when both mutations are present in progenitor cells. We exploit these findings to validate a combination treatment strategy targeting the epigenetic deregulation caused by loss of TET2 and the constitutively active KIT receptor for the treatment of patients with aggressive SM.